2021
DOI: 10.1111/dth.15279
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic vasculitis after COVID ‐19 vaccination

Abstract: Leukocytoclastic vasculitis (LCV) is the vasculitis of small vessels. In this report, we describe a 38-year-old male patient who presented to our outpatient clinic with a 1-week history of rash on his lower extremities that had started 4 days after receiving the Pfizer-BioNTech SARS-CoV-2 vaccine. A diagnosis of LCV was made based on clinical and histopathological findings. The patient was treated with antihistamines and prednisolone, after which improvement was observed in the lesions. With this paper, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty cases of COVID‐19‐vaccine triggered‐LCV were noted; three with an elevated anti‐Spike SARS CoV‐2 Antibody titer, two of them had no history of COVID‐19.Oral mucosal involvement was noted in one case. Only one had cryoglobulinemia 7,18–33,36,37 . Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…The patients presented more severe manifestations, including massive rhabdomyolysis, necrotizing vasculitis, and acute kidney injury, and required specific treatments such as intravenous steroids, Rituximab, and cyclophosphamide. Other authors described leukocytoclastic vasculitis after exposure to a COVID-19 vaccine, presenting with purpuric lesions and palpable papules, requiring antihistamines and prednisolone [ 21 ]. Our patient instead maintained a normal kidney function, creatinine kinase levels were in range, and clinical examination did not find suspicious skin manifestations; it was not necessary to administer specific treatments apart from Levamisole discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Skin-limited small vessel vasculitis or LCV (56) represents the most common CV reported after anti-SARS-CoV-2 vaccination. It has been observed after the Pfizer-BioNTech mRNA vaccine (BNT16B2b2) (57)(58)(59)(60)(61)(62)(63)(64)(65). Moderna mRNA 2).…”
Section: Cutaneous Small-vessel Vasculitismentioning
confidence: 99%